Effect of soybean oil supplementation on nutrient utilization, milk yield and its quality in lactating crossbred cows - MEWARA, KOUSHAL K; KUMAR, ANIL; RAO, P V RAMAN; TIWARI, D P (The Indian Journal of Animal Sciences, 2011)
Lactating crossbred cows (18) yielding 10 to 15 litres milk daily during mid lactation were divided into 4 groups of 4 animals each to study the influence of soybean oil supplementation on milk yield, its quality, serum lipid profile and nutrients utilization in lactating crossbred cows. Animals in groups 1, 2, 3 and 4 were fed concentrate mixture containing 0 (control), 2, 4 and 6% soybean oil, respectively as per requirements along with mixed green fodder (oats + berseem, maize and sorghum + oats hay) ad lib. The experimental feeding trial lasted for 90 days. No significant differences were noticed among different groups for average total daily DM consumption which ranged from 12.76 to 13.03 kg/day. Ether extract digestibility was significantly higher in the soybean oil supplemented groups than control group while there was no significant difference in the digestibility of other proximate components. Highest milk yield, 4% FCM, ECM, fat, protein and SNF yields were recorded in group 3, however, these values did not differ significantly amongst the different groups. The average total solids, solids-not-fat, fat and lactose contents of milk increased significantly in group 3 as compared to other groups. Gross energetic efficiency for milk production under group 3 was significantly higher than other groups while no significant difference was found for the net energetic efficiency. The gross and net efficiency of nitrogen utilization for milk production ranged from 19.78 to 22.89 and 28.20 to 32.24%, respectively, being highest in group 3 but no significant difference was noted among the groups. Total fat content in serum was significantly higher in cows fed rations supplemented with soybean oil than control. Free fatty acids and iodine number in serum did not differ significantly among different groups but increased linearly with increase in supplementation of soybean oil in the ration. The total unsaturated fatty acids also increased in the milk with addition of soybean oil. It can be concluded that soybean oil supplemented ration caused slight improvement in the yields of milk, 4% FCM, ECM, fat, protein and SNF in milk of cows fed at 4% level in concentrate mixture without any effect on the digestibility of nutrients. Significant increase in concentration of total unsaturated fatty acids in milk fat indicates the improvement in milk quality.